2009
DOI: 10.1111/j.1740-8261.2009.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contrast‐enhanced Computed Tomography to Assess Angiogenesis in Deep Digital Flexor Tendonopathy in a Horse

Abstract: We compared contrast-enhanced computed tomography (CT) and high field magnetic resonance (MR) imaging in a horse with deep digital flexor tendonopathy. Lesions in the distal extremity were documented grossly and histopathologically. In contrast-enhanced CT, the deep digital flexor tendon lesions were markedly contrast enhancing with evidence of angiogenesis in the core and dorsal border lesions. The lesion morphology was clearly delineated on MR imaging, but without contrast media angiogenesis cannot be identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 27 publications
4
68
1
1
Order By: Relevance
“…Intra‐arterial CECT is a novel technique and, although not critical to the diagnosis of axial lysis, allowed for further characterisation of the regional soft tissues, osseous and synovial structures. Contrast‐enhanced CT provides qualitative, functional information regarding the nature and influence of the regional vasculature through indirect evidence of vascular leakage (tissue contrast) or neovessel formation (small caliber new vessels) . As imaged in this study, the majority of horses with PL abnormalities had functional abnormalities further confirming the presence of tissue injury and repair in the PL and the suspensory branches.…”
Section: Discussionsupporting
confidence: 64%
“…Intra‐arterial CECT is a novel technique and, although not critical to the diagnosis of axial lysis, allowed for further characterisation of the regional soft tissues, osseous and synovial structures. Contrast‐enhanced CT provides qualitative, functional information regarding the nature and influence of the regional vasculature through indirect evidence of vascular leakage (tissue contrast) or neovessel formation (small caliber new vessels) . As imaged in this study, the majority of horses with PL abnormalities had functional abnormalities further confirming the presence of tissue injury and repair in the PL and the suspensory branches.…”
Section: Discussionsupporting
confidence: 64%
“…More recently, it was suggested that angiogenesis in tendon lesions could be more clearly identified with contrast enhanced CT than MRI. Contrast CT may offer a more simple and inexpensive technique to document changes in vascular permeability and blood flow associated with healing of tendon lesions (Puchalski et al . 2009)…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Recent information suggests that the distinction between acute and chronic lesions may be best facilitated with the use of intravenous MRI or intra‐arterial CT contrast (Judy et al . 2008; Puchalski et al . 2009).…”
Section: Treatment and Outcomementioning
confidence: 99%
“…2009). New protocols, including the use of intra‐arterial contrast medium infusion (Puchalski et al . 2009), have been established to improve the diagnostic value of this modality, but it remains so far less effective than MRI for detecting soft tissue injuries.…”
Section: Discussionmentioning
confidence: 99%